Removal of ciprofloxacin from an aqueous medium by adsorption on natural and hydrolyzed bentonites - Jara-Cobos, Lourdes; Abad-Delgado, David; Ponce-Montalvo, Jonathan; Menendez, Miguel; Peñafiel, María E. (Frontiers in Environmental Science, 2023)
Two bentonites (sodic bentonite, BSN, and calcic bentonite, BCN) were treated with nitric acid to improve the adsorption capacities using ciprofloxacin (CIP) as an adsorbate. The results demonstrated that nitric acid treatment enhances the specific area and increases the pore volume of both bentonites. The mechanism of adsorption of CIP was investigated using a kinetic model, isotherms, and pH influence. The adsorption capacity for BSN increased from 294.1 mg.g−1 to 416.6 mg.g−1 after acid treatment, while the increase in the adsorption capacity of BCN was minor. The increase in CIP removal may be due to an increase in the specific area and the presence of acidic surface functional groups. The adsorption mechanism of CIP on all adsorbents was governed by external diffusion, internal diffusion, and adsorption to reach equilibrium. The adjustment of strong adsorbents to the BET model indicated multilayer adsorption. The best adsorbent is sodic bentonite with nitric acid treatment. The study of the pH effect showed that the mechanism of CIP adsorption is hydrogen bonds and electrostatic interaction. Therefore, the acid treatment was found promising to improve the adsorbent characteristic of clays for removing CIP from water.